Evaluating the effect of virgin coconut oil pulling on viral load, bacterial load and inflammatory mediator levels in chronic periodontitis – A clinical study - Monika M; Rudhra K; Vennila K; Elanchezhiyan; Sri Harini P; S. Shakeron (Journal of Oral Biology and Craniofacial Research)
Background and objective: Periodontitis and dental caries are among the most prevalent oral diseases, with chronic periodontitis being a multifactorial, infectious condition that leads to inflammation in the supporting structures of the teeth, progressive attachment loss, and bone resorption. Chronic periodontitis is driven by a consortium of pathogenic microorganisms. This study aimed to evaluate the efficacy of virgin coconut oil (VCO) pulling in reducing the microbial load and inflammatory mediators responsible for chronic periodontitis, in comparison to chlorhexidine (CHX) mouthwash and distilled water. Methods: Thirty patients diagnosed with chronic periodontitis were randomly allocated into three groups. Group A served as the control and used distilled water for oral rinsing, Group B used chlorhexidine mouthwash, and Group C performed oil pulling with virgin coconut oil. Pre-operative subgingival plaque samples were collected from all participants, followed by complete scaling and root planing. Post-operative samples were collected after four weeks. Both pre- and post-treatment samples were subjected to real-time PCR (rtPCR) and enzyme-linked immunosorbent assay (ELISA) to quantify viral and bacterial loads, as well as levels of key inflammatory mediators. Results: A significant reduction in viral load, bacterial load, and inflammatory mediators was observed in both the VCO and CHX groups compared to the distilled water group. The reductions in the VCO and CHX groups were statistically significant, with comparable efficacy between the two interventions. Conclusion: Virgin coconut oil pulling demonstrated a significant reduction in microbial and inflammatory markers in patients with chronic periodontitis, showing similar efficacy to chlorhexidine mouthwash. Given its comparable therapeutic effects and reduced side effect profile, VCO presents a viable alternative to chlorhexidine for managing chronic periodontitis.